Analisis Faktor-Faktor Yang Mempengaruhi Minat Beli Konsumen Di Toko SRC Kota Yogyakarta - Damanik, Fransius Awaldo (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
This study aims to determine whether service quality, store image, and store atmosphere affect consumer buying interest at SRC stores in Yogyakarta City. The population in this study were respondents who had shopped at the SRC store in Yogyakarta City. This type of research uses qualitative research with data collection methods through interviews. The sampling method in this study used the accidental random sampling method, namely taking samples from members of the population at random, a population that can be found easily and who are happy to provide it. The number of samples taken is 60 respondents. Based on the conclusions of this study, it shows that the Service quality has no positive and insignificant effect on consumers' buying interest in SRC stores. While the variables of store image and store atmosphere have a positive and significant effect on consumer buying interest at the SRC store in Yogyakarta City, and the variables of service quality, store image and store atmosphere simultaneously have a significant effect on consumer buying interest at the SRC store in Yogyakarta City. The ability of the independent variable in explaining the dependent variable, which is 75.2%, the remaining 24.8%, is explained by other variables not discussed in this study, such as the distance between the SRC store and the people who shop at the store.